2010
DOI: 10.1103/physrevb.81.054117
|View full text |Cite
|
Sign up to set email alerts
|

Deformation mechanisms and pseudoelastic behaviors in trilayer composite metal nanowires

Abstract: The deformation mechanisms in Cu-Ni-Cu composite nanowires subjected to uniaxial tensile loading are investigated using molecular-dynamics simulations. We particularly explore the coupled effects of geometry and coherent interface on the tendency of nanowires to deform via twins and show pseudoelastic behavior. It is found that the critical size to exhibit pseudoelasticity in composite nanowires is 5.6ϫ 5.6 nm 2 , which is 6.5 times greater than single-crystalline Cu nanowires. Our results also show that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The confined layer slip (CLS) model suggests that in some cases having layer thicknesses on the order of 20 nm will lead to dislocation motion being constrained to individual layers, due to the dissimilar elastic properties of the layers, rather than allowing dislocations to propagate across interfaces [21]. Furthermore, in certain structures such as Cu-Ni, a nanowire consisting of a copper core with a Ni shell can exhibit pseudoelasticity at large strains due to twinning [22][23][24]. Therefore, it may be possible to increase strength or relative ductility in nanoporous materials by synthesizing ligaments that consist of a coreshell structure of a nanolayered metal; a composite foam, if it behaves like a metallic multilayer, should exhibit more strain hardening capacity than the single material system [20].…”
Section: Introductionmentioning
confidence: 99%
“…The confined layer slip (CLS) model suggests that in some cases having layer thicknesses on the order of 20 nm will lead to dislocation motion being constrained to individual layers, due to the dissimilar elastic properties of the layers, rather than allowing dislocations to propagate across interfaces [21]. Furthermore, in certain structures such as Cu-Ni, a nanowire consisting of a copper core with a Ni shell can exhibit pseudoelasticity at large strains due to twinning [22][23][24]. Therefore, it may be possible to increase strength or relative ductility in nanoporous materials by synthesizing ligaments that consist of a coreshell structure of a nanolayered metal; a composite foam, if it behaves like a metallic multilayer, should exhibit more strain hardening capacity than the single material system [20].…”
Section: Introductionmentioning
confidence: 99%
“…Abdolrahim and Mastorakos [87,174] have studied the interface enhancement effect in Cu-Ni-Cu sandwiched composite nanowires. The interface is parallel to the wire axis direction and resembles that in the core-shell configuration but with less structural symmetry.…”
Section: Interface-enhanced Pseudo-elasticity In Layered Composite Namentioning
confidence: 98%
“…Hence, surface effects are dominant factors affecting the structure of nanowires and can even induce thorough structural transition. On the heels of these discoveries, other interesting materials properties such as surfaceinduced lattice reorientation, martensitic phase transformation (MT), pseudo-elastic behavior, and shape memory effects (SMEs) have been studied and observed from fcc [14,[19][20][21][22][23]28,[63][64][65][66][67][68][69][70][71][72][73][74][75], bcc [76][77][78][79][80][81][82], and hcp [83,84] single-element, layered composite [85][86][87][88][89], intermetallic alloy [90][91][92][93][94][95], and even metal oxide [96][97][98][99][100] or nitride [101] compound nanowires. The reversible strain can be as high as 40-70% and is much lar...…”
Section: Size-dependent Structural Stability Of Nanomaterialsmentioning
confidence: 99%
“…In two previous papers 1, 2 we studied the possibility of increasing the critical dimensions of nanowires for exhibiting pseudoelasticity by adding the coherency stresses found in coppernickel (Cu-Ni) interfaces, using molecular dynamics (MD) simulations. In particular, our simulations showed that trilayer composite nanowires, made of alternating copper and nickel layers, would still exhibit pseudoelastic behavior for total thicknesses that are about 3 times larger than that of single crystalline nanowires 2 .…”
mentioning
confidence: 99%